O mapeamento de processos para a melhoria contínua dos serviços nas coordenações de curso do CCSA/UFPB - Souto, Alex de Araújo (2017)
It is presented the business process mapping of the processes started in the Coordination of Undergraduate Courses of the Center for Social Applied Sciences in the Federal University of Paraíba, whose petitioners are the undergraduate students. Business process mapping is intended to standardize these processes in relation to the needed documents, procedural protocols and use of the Integrated System of Patrimony, Administration and Contracts (SIPAC). It is aimed to improve the process management in the Coordination of Undergraduate Courses of the CCSA/UFPB, by means of the business process management, collaborating with the process of organizational learning in these sectors. The main objective is to study a model of business process mapping started in the Coordination of Undergraduate Courses of the CCSA/UFPB, which is based on the rules of the UFPB, making a basis for an efficient information management. The specific ones include the identification of the processes generated in the Coordination of Undergraduate Courses; the description of the selected processes, based on the Resolution n. 16/2015 CONSEPE/UFPB and related documents; to map the chosen processes; to elaborate business process maps aiming the standardization of work in these sectors, by means of the Bizagi software; to show how business process management can contribute with information management in the Coordination of Undergraduate Courses of the UFPB. The methodology includes a descriptive study with qualitative approach, which adopted document research in the regulations of the UFPB about the undergraduate courses and the use of the SIPAC, in order to produce the business process maps originated in the Coordination of Undergraduate Courses of the CCSA/UFPB, by means of Bizagi software, constituting in an applied research. The research is motivated by the work of the researcher as a civil servant of a Coordination of Undergraduate Course where, by means of participant observation, there were identified the reasons for its execution, in order to attend to the institutional demands and in accordance to the objectives of a Professional Master Course. Next, it was done a document analysis of the Resolution n. 16/2015 CONSEPE/UFPB, based on the Content Analysis of Bardin, specifically in the common points between them. The results led to the identification of six processes that start in the Coordination of Undergraduate Courses. They were described and the elaboration of business process maps was a consequence, reaching the objectives proposed in this work. As a consequence, the resultant product of this work can be made available to the Coordination of Undergraduate Courses of the UFPB, as well as it could be added to the SIPAC. In both cases, it will facilitate the use of the system for the selected processes, promoting the relation between information management and business process management, besides the collaboration with organizational learning in the UFPB. With this work, therefore, it is expected that this could be the first step in the direction for the business process management in the university, what may lead to better services.